A Risk Scoring Model for High-Dose Methotrexate-Induced Liver Injury in Children With Acute Lymphoblastic Leukemia Based on Gene Polymorphism Study - He, Xia; Yao, Pingli; Li, Mengting; Liang, Hong; Liu, Yilong; Du, Shan; Zhang, Min; Sun, Wenzhuo; Wang, Zeyuan; Hao, Xin; Yu, Ze; Gao, Fei; et al. (Frontiers in Pharmacology, 2021)
A study on 70 acute lymphoblastic leukemia (ALL) children (age ≤ 16 years) treated with high-dose methotrexate (HD-MTX) in Sichuan Provincial People's Hospital was conducted. The aim of the study was to establish a risk scoring model to predict HD-MTX-induced liver injury, considering of gene polymorphisms’ effects. Data screening was performed through t-test, chi-square test and ridge regression, and six predictors were identified: age, MTRR_AA, MTRR_AG, SLCO1B1_11045879_CC, albumin_1 day before MTX administration, and IBIL_1 day before MTX administration (p < 0.1). Then the risk scoring model was established by the ridge regression and evaluated the prediction performance. In training cohort (n=49), the area under the curve (AUC) was 0.76 and metrics including accuracy, precision, sensitivity, specificity, positive predictive value and negative predictive value were promising (0.86, 0.81, 0.76, 0.91, 0.81, 0.88, respectively). In test cohort (n=21), the AUC was 0.62 and negative predictive value was 0.80, other evaluation metrics were not satisfactory, possibly due to the limited sample size. Ultimately, the risk scores were stratified into three groups based on their distributions: low-risk (≤ 48), medium-risk (49~89), and high-risk (> 89) groups. This study could provide knowledge for the prediction of HD-MTX-induced liver injury and reference for the clinical medication.